INTERPERSONAL DIALOGUE TO BUILD STUDENTS’ ABILITY IN USING ENGLISH - Hidayati, Nurul (Jurnal Ilmiah Spectral, 2020)
This study aims to saw the implementation of interpersonal dialogue inlearning English to enhance students' ability in using the English language. This study used a qualitative method. The data collection technique used observation techniques to saw the process of the implementation of learning to uses interpersonal dialogue, and interview techniques to determine the impact of implementing interpersonal dialogue. Respondents in this study were lecturers and students. The results showed that during the learning process, the interpersonal dialogue was created between students and students and the lecturer. Then, there is an increase in learning activities, student participation, students get additional knowledge in the form of vocabulary, grammar, pronunciation, and self-confidence. In conclusion, the implementation of interpersonal dialogue can build communicative learning, because of the interactive communication between students and lecturers, as well as students and students during the learning process. As well as increasing student ability and student confidence in using English.